Three-dimensional analysis of the angular momentum of a pole-vaulter - Morlier, J.; Cid, M. (Journal of Biomechanics, 1996)
A method to determine the three orthogonal components of the angular momentum of a human body about its center of gravity is applied to the pole-vault. The angular momentum and the pole force are used in the analysis of pole-vaulting and are also compared with Gros's data (1982, Ph.D. thesis, University of Alberta) and Hubbard and Barlow's results (1980, Proc. Biomechanics Symp. Indian State Board of Health, pp. 33-48). This study tries to show how such results can be useful in many sporting activities and are necessary for optimization of athletic movement.